2017
DOI: 10.3892/mmr.2017.6149
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-410 regulates autophagy-related gene ATG16L1 expression and enhances chemosensitivity via autophagy inhibition in osteosarcoma

Abstract: Osteosarcoma, which is the most common type of primary bone tumor in adolescents, is characterized by complex genetic alterations and frequent resistance to conventional treatments. MicroRNAs (miRs) have emerged as fundamental regulators in gene expression through their ability to silence gene expression at post-transcriptional and translational levels. The present study investigated the role of miR-410 in the progression of osteosarcoma. The results demonstrated that the expression of miR-410 was markedly dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…For example, miR-30d has been found to suppress autophagy in human cancer cells by inhibiting autophagy pathway-related genes, such as ATG12, ATG5 and ATG2; autophagosome formation; and the conversion of Lc3B-I to Lc3B-II (36). Furthermore, ATG16L1 plays an important role in autophagy and a previous study verified that suppression of autophagy by miR-410 overexpression in osteosarcoma cells was achieved partly through downregulation of ATG16L1 (17). Importantly, Xu et al (37) found that ATG4B is an underlying target gene of let-7i and that overexpression of let-7i could inhibit autophagic activity in preeclampsia through downregulation of ATG4B.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, miR-30d has been found to suppress autophagy in human cancer cells by inhibiting autophagy pathway-related genes, such as ATG12, ATG5 and ATG2; autophagosome formation; and the conversion of Lc3B-I to Lc3B-II (36). Furthermore, ATG16L1 plays an important role in autophagy and a previous study verified that suppression of autophagy by miR-410 overexpression in osteosarcoma cells was achieved partly through downregulation of ATG16L1 (17). Importantly, Xu et al (37) found that ATG4B is an underlying target gene of let-7i and that overexpression of let-7i could inhibit autophagic activity in preeclampsia through downregulation of ATG4B.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, autophagy-related 16-like 1 (ATG16L1) has been identified as an autophagy-related gene that can regulate autophagosomes (16). ATG16L1 belongs to a class of protein complexes that are considered vital for autophagy (17). Emerging data has illustrated the functionality of ATG16L1 in the development of atherogenesis (18).…”
Section: Introductionmentioning
confidence: 99%
“…In cisplatin-resistant osteosarcoma cells, chloroquine could block autophagy and increase chemosensitivity [43]. Autophagy inhibitor 3-MA combined with doxorubicin or cisplatin could improve the therapeutic response to chemotherapy drugs in U2OS, Sao-2, and MG63 osteosarcoma cell lines [10, 44]. Therefore, enhancing the level of p62 may be an effective therapy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a type of non-coding RNAs with regulatory function and a length of approximately 20-25 nucleotides, which identify target mRNAs according to the principle of complementary base pairing and guide silencing complex to degrade target mRNAs or repress translation of mRNAs (5). Increasing studies found that miRNAs played an important role in specific cellular processes such as cell differentiation, morphosis and neoplasia (6). In human cancer, a miRNA can be an oncogene or a cancer suppressor gene in the process of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%